The viability of green bonds as a financing mechanism for green buildings in ASEAN - Anant Kapoor; En-Qi Teo; Dina Azhgaliyeva; Yang Liu (Asian Development Bank Institute (ADBI), 2020)
As the growth of energy demand outstrips that of energy supply in Southeast Asia, it becomes imperative for ASEAN member states to seek energy efficiency improvements for sustained energy security. While green buildings have an overall low penetration rate in ASEAN, when compared to the rest of the world, a relatively large proportion of green bond proceeds in ASEAN have been channeled to financing green buildings. Green bonds hold vast potential as a financing mechanism, and the importance of green bonds as a funding source for green buildings in ASEAN is projected to increase in the future. ASEAN governments can encourage the use of this source of finance to address underinvestment in green buildings through providing information on raising funds through green bonds, endorsing investment in green buildings through codifying green building standards, and promoting local currency bond financing through domestic investors.
Keywords: Q28; Q42; Q43; Q53; G2; G3; 330; green buildings; green bonds; energy efficiency; ASEAN; green sukuk; ICMA green bond principles; ASEAN green bond standards; sustainable finance